The Diagnosis and Treatment of Branch Retinal Vein Occlusions: An Update - Diana-Maria Darabuş; Rodica Georgiana Dărăbuş; Mihnea Munteanu (Biomedicines)
Branch retinal vein occlusion (BRVO) is a common retinal vascular condition and a significant contributor to vision loss worldwide, particularly in middle-aged and elderly populations. This review synthesizes current knowledge on the epidemiology, pathogenesis, and clinical features of BRVO, alongside recent advancements in diagnostic and therapeutic strategies. BRVO is approximately four times more prevalent than central retinal vein occlusion (CRVO) and often leads to significant vision impairment. By focusing on BRVO, this review aims to address the specific challenges and advancements in its diagnosis and management. The pathophysiology of BRVO is complex, involving factors such as venous compression, inflammation, and increased levels of vascular endothelial growth factor (VEGF). Diagnostic approaches such as optical coherence tomography (OCT) and fluorescein angiography are highlighted for their roles in assessing disease severity and guiding treatment decisions. Therapeutic interventions, including laser photocoagulation, anti-VEGF therapy, and intravitreal corticosteroids, are critically evaluated, emphasizing emerging treatments such as gene therapy, peptide-based agents, and small-molecule inhibitors. Despite advancements in management strategies, the recurrence of macular edema and treatment resistance remain significant challenges. Continued research is essential to refine therapeutic protocols and improve long-term visual outcomes for patients with BRVO.